Mental health in the hadith spotlight: enlightenment for a healthy soul - Yuliharti Yuliharti; Agustiar Agustiar; M. Ridwan Hasbi; Syafi'ah Syafi'ah; Usman Usman; M. Fahli Zatrahadi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research aims to explore the concept of mental health from a hadith perspective, which is an important part of Islamic teachings. Using literature research methods, this study analyses various hadiths that are relevant to understanding the principles of mental health taught by the Prophet Muhammad. We thoroughly studied a total of 12 articles and 3 books related to this topic. The research results show that mental health in the hadith includes principles such as feelings of security, independence, responsibility, and physical and spiritual balance. These hadiths illuminate the significance of preserving mental health in the pursuit of life, emphasizing the need for appreciation and care. This study contributes to the development of a spiritual understanding of mental health, as well as offering guidance for Muslims in maintaining mental well-being based on hadith teachings.